2019
DOI: 10.3389/fpsyg.2019.01976
|View full text |Cite
|
Sign up to set email alerts
|

Musicians Show Better Auditory and Tactile Identification of Emotions in Music

Abstract: Musicians are better at processing sensory information and at integrating multisensory information in detection and discrimination tasks, but whether these enhanced abilities extend to more complex processes is still unknown. Emotional appeal is a crucial part of musical experience, but whether musicians can better identify emotions in music throughout different sensory modalities has yet to be determined. The goal of the present study was to investigate the auditory, tactile and audiotactile identification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
1
6
1
Order By: Relevance
“…Although participants in the music training group became more accurate and faster at recognising the expressed emotion by the end of the study, so did participants in the control group without music, suggesting that such improvements could be merely a result of task repetition. Musicians' emotion processing advantage has been shown primarily for music excerpts 25,26,86 and speech prosody 10,39 , which involve the processing of sound features shared by music and speech 87,88 . Also, our results are in line with those of Correia et al 32 showing that musicians did not have an advantage when recognising emotions from facial expressions, and with recent evidence showing that musicians are not better than non-musicians in recognising emotions from people's movement and gestures 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although participants in the music training group became more accurate and faster at recognising the expressed emotion by the end of the study, so did participants in the control group without music, suggesting that such improvements could be merely a result of task repetition. Musicians' emotion processing advantage has been shown primarily for music excerpts 25,26,86 and speech prosody 10,39 , which involve the processing of sound features shared by music and speech 87,88 . Also, our results are in line with those of Correia et al 32 showing that musicians did not have an advantage when recognising emotions from facial expressions, and with recent evidence showing that musicians are not better than non-musicians in recognising emotions from people's movement and gestures 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Facial and body expressions are essential to musical performance and are used by musicians to communicate between co-performers and audiences 22 . Consequently, musical expertise has been found to have an enhanced effect on emotion processing for musical stimuli 23 25 . The current consensus is that musicians can better perceive and categorise musical emotions than non-musicians 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Vibroacoustics is increasingly used to enhance the affective and emotional experience of music for listeners. 12,13,44 In line with this, providing tactile stimulation may enhance the positive emotions of preferred music and increase the likelihood that topdown affective and motivation mechanisms would attenuate negative aspects of the pain experience such as its intensity or unpleasantness. In the growing search for non-pharmacological interventions for acute and chronic pain in real-world situations (e.g.…”
Section: Discussionmentioning
confidence: 91%
“…Firstly, we assumed that tactile stimulation by itself can induce emotion in listeners. This assumption was based on a study by Sharp et al 44 who demonstrated that both musicians and non-musicians were able to recognize emotions via tactile stimulation above chance for music that induced emotions of happiness and fear. It may be worthwhile in future studies to measure the characteristics of the tactile stimulation extracted from music and determine which characteristic may modulate pain experience as done for the acoustic properties of music.…”
Section: Discussionmentioning
confidence: 99%
“…[16], [17], [18], [19]), other studies found an effect of musical training on musical emotion recognition accuracy (e.g. [5], [20], [21], [22], [23]). This calls for more research on the musical expertise of the listeners as a possible predictor for emotion decoding abilities in music.…”
Section: Psychological Studiesmentioning
confidence: 90%